Optimizing Economic Management amid Globalization: A Bibliometric Review of the Emerging Trends (2020-2025) - Zahara Tussoleha Rony; Musdirwan Musdirwan; Loso Judijanto; Ignatius Septo Pramesworo; Yanti Setianti (Universitas Islam Negeri Raden Mas Said Surakarta, 2025)
Amid increasing global interdependence and complex socioeconomic challenges, the need for effective and adaptive economic management has grown more urgent. Although academic interest in globalization and economic governance is rising, a comprehensive synthesis of current research trends remains limited. This study addresses that gap by systematically synthesizing how global developments are reshaping economic management discourse. Employing a bibliometric and conceptual review approach, the study examines 1,698 publications from major academic databases (e.g., Scopus, JSTOR, Google Scholar) between 2020 and 2025. A structured search strategy and rigorous screening criteria were applied to ensure relevance and quality. Thematic and bibliometric analyses were used to identify emerging trends in keyword usage, authorship patterns, international collaboration, and disciplinary focus. Key findings highlight sustainability, renewable energy, and public policy as dominant themes in contemporary economic management research. The study also reveals a growing emphasis on interdisciplinary and cross-border approaches, reflecting the complex realities of globalized economies. Notably, the persistent tension between economic growth and environmental protection indicates the need for adaptive, evidence-based policy frameworks.